The Role of Women in Agricultural Activities in Anjir Serapat Muara 1 Village - Azizah, Intan Noor; Syaharuddin, Syaharuddin; Handy, Muhammad Rezky Noor; Mutiani, Mutiani; Rahmia, Sovia Husni (Universitas Lambung Mangkurat, 2024)
Agricultural activities are synonymous with the physical strength of men compared to women. However, over time, women also have a role in agricultural activities. Therefore, it is necessary to learn about gender studies. Learning about gender can be found in the role of women in agricultural activities. The role of women in agricultural activities in Anjir Serapat Muara 1 Village can be used as an example of gender equality. This research aims to describe the role of women farmers in agricultural activities in Anjir Serapat Muara 1 Village. The method applied by the author in this research is a qualitative approach with the use of descriptive methods. The research location is Anjir Serapat Muara 1 Village, Barito Kuala Regency, South Kalimantan Province with the subject of Anjir Serapat Muara 1 Village women. The research instrument here is the researcher himself with the use of observation data collection techniques about the role of women in agriculture, interviews, and documentation used in the form of village profile data archives and moments during research related to the role of women in agricultural activities. The results of this study state that the role of women in agricultural activities in Anjir Serapat Muara 1 Village is due to hereditary factors, namely because being a farmer in this village is used as the main livelihood because the village area is suitable for agriculture and business factors to improve the family economy, namely with the aim of helping to ease the burden on husbands or female farmers who act as heads of families caused by husbands who have died or have divorced.